Trunk muscle activation of core stabilization exercises in subjects with and without chronic low back pain - Ylinen, Jari; Pasanen, Tero; Heinonen, Ari; Kivistö, Heikki; Kautiainen, Hannu; Multanen, Juhani (Journal of back and musculoskeletal rehabilitation, 2024)
Weakness and atrophy in trunk muscles have been associated with chronic low back pain (CLBP). This study aimed to identify isometric exercises resulting the highest trunk muscle activity for individuals with and without CLBP. Fourteen males with CLBP and 15 healthy age-matched healthy subjects were recruited for this study. Muscle activity during maximal voluntary isometric contraction (MVIC) was measured for a comparative reference with surface electromyography (sEMG) from six trunk muscles. Thereafter maximum EMG amplitude values were measured during eleven trunk stability exercises. The maximal EMG activity in each exercise relative to the MVICs was analyzed using generalizing estimating equations (GEE) models with the unstructured correlation structure. The GEE models showed statistically significant differences in muscle activity between exercises within both groups (p< 0.001), with no significant differences between groups (p> 0.05). The highest muscle activity was achieved with the hip flexion machine for multifidus, side pull with a resistance band for lumbar extensors, side and single-arm cable pull exercises for thoracic extensors, rotary plank and the hip flexion machine for abdominal. This study found five isometric trunk exercises that exhibited highest muscle activity depending on muscle tested, with no significant difference between individuals with and without CLBP.